Simple, Powerful Strategies for Student Centered Learning [electronic resource] - Jacobs, George Martin; Renandya, Willy Ardian; Power, Michael; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book reminds us teachers about all the little things we can do to be more student-centric. It shows teachers how to ?walk the walk,? and shows teacher educators how to guide colleagues along a student-centered path. The book examines why we should and how we can promote student-student interaction to enable students to learn more and enjoy the process. It also offers simple but effective strategies for enhancing student motivation, a factor that many experts consider to be the most important determinant of success in educational endeavors. In addition, it examines diversity, particularly the many differences that exist among students, and explains simple, easy strategies for how this diversity can be not only taken into consideration, but actively celebrated.
1. Teachers and Students as Co-Learners -- 2. Student-Student Interaction -- 3. Learner Autonomy -- 4. SCL via the prism of the element of Focus on Meaning -- 5. Curricular Integration -- 6. Diversity -- 7. Thinking Skills -- 8. Alternative Assessment -- 9. Learning Climate -- 10. Simple, powerful strategies for enhancing student Motivation -- Conclusion. {uE035}
Keywords: Education; Educational sociology; Teaching